4n-2=12-4n

Simple and best practice solution for 4n-2=12-4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-2=12-4n equation:


Simplifying
4n + -2 = 12 + -4n

Reorder the terms:
-2 + 4n = 12 + -4n

Solving
-2 + 4n = 12 + -4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4n' to each side of the equation.
-2 + 4n + 4n = 12 + -4n + 4n

Combine like terms: 4n + 4n = 8n
-2 + 8n = 12 + -4n + 4n

Combine like terms: -4n + 4n = 0
-2 + 8n = 12 + 0
-2 + 8n = 12

Add '2' to each side of the equation.
-2 + 2 + 8n = 12 + 2

Combine like terms: -2 + 2 = 0
0 + 8n = 12 + 2
8n = 12 + 2

Combine like terms: 12 + 2 = 14
8n = 14

Divide each side by '8'.
n = 1.75

Simplifying
n = 1.75

See similar equations:

| 7(15x+25y)=125 | | x^2+4y^2=144 | | -12=3(x)-6 | | 12x+6=4x-20-2 | | 5+3y=30 | | -24=3(x)-6 | | 2x^2y+8xy-58y=0 | | 5x+55=7x+185 | | 2(7h-5)=24+9h | | -2x+19+5x-11= | | 9(x-2)-3=-21 | | Y=z+20 | | 3x+0.5=-8 | | 5x+55=7x+180 | | 4x^2+3x^2=441 | | -9+(-9)=x | | -5=n+2-6 | | 5y=-1-3x | | 5x+3y=30-5x | | -y-y-y-y= | | 2(-16+2x)=x-5 | | 5-4[9-(6y-3)]= | | 3y=5+12 | | 3x+0.5=8 | | N+3=-5+2n+7+4 | | 5x+93+2x=7x+54 | | 4+8(1+6c)=16 | | 6p+9=-9 | | 30-p=p+10 | | 20+p=p+10 | | 3y=-6x+8 | | 24b-22=-4(1-6b) |

Equations solver categories